Optimalisasi Literasi Keuangan, Modal Usaha, Dan Pengelolaan Keuangan Terhadap Keberlangsungan Umkm Sektor Kuliner Kota Sorong Provinsi Papua Barat Daya - Waode Nurma Inda Aprilia Sari; Vebby Anwar; Andi Sismar; Andi Irwan (STIM-LPI Makassar, 2026)
This study aims to determine the influence of financial literacy, business capital, and financial management on the sustainability of culinary MSMEs in Sorong City, both partially and simultaneously. This study used a quantitative approach with a sample of 100 culinary MSMEs. The sampling technique used purposive sampling, while data analysis was conducted using multiple linear regression using SPSS. The results showed that partially, business capital and financial management had a positive and significant effect on MSME sustainability, while financial literacy had no significant effect. Simultaneously, these three variables significantly influenced MSME sustainability, with a coefficient of determination of 80.2%, meaning the model was able to explain 80.2% of business sustainability, while the remainder was influenced by other variables outside this study. The findings of this study indicate that the sustainability of culinary MSMEs in Sorong City is determined more by capital capacity and the quality of financial management than by theoretical financial literacy. Therefore, increasing access to capital, practice-based financial management training, and mentoring programs are key to strengthening the resilience and growth of MSMEs. Keywords: Financial Literacy, Business Capital, Financial Management, Sustainability of MSMEs.